What Motivates Students About Open Pedagogy? Motivational Regulation Through the Lens of Self-Determination Theory - Eric Werth (Athabasca University Press, 2021)
Open pedagogy is growing in popularity as an instructional method to decentralize classroom power dynamics, engage students, and provide greater meaning to student work. To investigate the impact of open pedagogy on motivation, interviews were conducted with first-year college students at a four-year liberal arts college after completing a semester-long project based on this pedagogical approach. Student responses were assessed using self-determination theory as a theoretical framework, particularly in relation to the motivation regulatory styles displayed by research participants. Results indicate that students experienced various forms of extrinsic motivation during the project based on open pedagogy, with autonomous forms of regulation being more prevalent than controlled regulation. Interview data also suggest that agency plays a role in mediating the internalization of student motivation. Based on these findings, suggestions are provided to the design of assignments in general and open pedagogy specifically to enhance development of autonomous forms of motivation.